Impacts of HR Practices on Organizational Commitment: The Mediating Role of Organizational Culture - Iqbal, Shuja; Yun, Tian Hong; Akhtar, Shamim; Ankomah, Fred Yaw Nyarko (Journal of Asian Business Strategy, 2020)
In the fierce competition among SMEs in developing countries, HR practices are crucial concerning organizational commitment. SMEs strive for competitive advantage in the industry through high commitment of their employees concerning corporate goals of the firm. This study examined the relationship between HR practices such as recruitment and selection, training, financial rewards and recognition and organizational commitment. The data were collected from 223 employees of SMEs using the quantitative approach based on the questionnaire data collection method. Data were further analyzed for results in Smart PLS, deploying structured equation model (SEM) technique. The results indicated that direct path relationships among HR practices, organizational commitment and organizational culture; organizational culture and organizational commitment were positive and significant. Moreover, the study also found that organizational culture positively mediates between the relationship of HR practices and organizational commitment. This adds in the existing knowledge of the chosen constructs and uniquely examines them in Pakistan’s context. Also, this study offers practical implications for SMEs to develop HR strategies to enhance organizational commitment.